Copper-tin alloy copper foil based on thermal stability characteristic, method, circuit board and device

By etching the striped crack structure in the copper-tin alloy film, the stable fixation problem of copper foil in the printed circuit board is solved, and the buffering and stable positioning functions are formed, deformation and fracture are avoided, and the stability of the circuit board is improved.

CN119172923APending Publication Date: 2024-12-20SHAANXI WESTERN NEW MATERIAL TECH CO LTD

Patent Information

Application Number
CN202411641847.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The stability and fixation of copper foil in printed circuit boards is easily caused by deformation and internal stress, affecting product performance.

Method used

The striped crack structures arranged in multiple arrays are etched in the copper-tin alloy film by laser etching. The sides of each striped crack are irregularly curved, the cross-section is bowl-shaped, and the protrusions are formed around the periphery. A buffer structure is formed to stabilize the positioning and disperse the deformation of the insulating layer.

Benefits of technology

By forming a buffer structure and stable positioning function, the copper foil is prevented from deformation and breaking caused by stress in the circuit board, the bonding force between the copper foil and the insulating layer is improved, and the stability of the circuit board is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119172923A_ABST
    Figure CN119172923A_ABST
Patent Text Reader

Abstract

According to the copper-tin alloy copper foil based on the thermal stability characteristic, the method, the circuit board and the device, before the copper foil coarsening layer is prepared, the crack structure is etched in the copper-tin alloy film sheet through the laser etching method, the copper-tin alloy copper foil is obtained, the crack structure comprises the multiple stripe crack parts arranged in an array mode, and the stripe crack parts are arranged on the surface of the copper foil coarsening layer. The edge side of each stripe crack part is in an irregular curve shape, the cross section of each stripe crack part is in a bowl shape, protruding parts are formed on the peripheries of the stripe crack parts, the average inner diameter of the protruding parts is smaller than the width of the stripe crack parts, and the height of the protruding parts is smaller than the concave depth of the stripe crack parts. Therefore, the problems that the copper foil is easy to break when the circuit board is collided and the product performance is affected due to the fact that the copper foil is fixed in the printed circuit board to form stress due to the coarsened surface at present and thus the printed circuit board is easy to deform after being used for a long time, and the copper foil is easy to generate internal stress while the binding force is relatively poor can be solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of copper foil preparation, and in particular to a copper-tin alloy copper foil, method, circuit board and device based on thermal stability. Background Art

[0002] Copper foil is widely used as a metal material in printed circuit boards. With the development trend of miniaturization of electronic devices, higher requirements are also more clear and specific. The stable fixation of copper foil in the printed circuit board and how to avoid the force formed by the copper foil fixed in the printed circuit board due to the roughened surface, which makes the printed circuit board prone to deformation after long-term use, and the copper foil is prone to internal stress while the bonding force is poor, which makes the copper foil easy to break when the circuit board is collided, affecting the product performance. Therefore, there are deficiencies. Summary of the invention

[0003] The present application provides a copper-tin alloy copper foil, method, circuit board and device based on thermal stability, aiming to solve the problem of stable fixation of copper foil in a printed circuit board and how to avoid the copper foil being fixed in the printed circuit board due to roughened surface to form stress, so that the printed circuit board is prone to deformation after long-term use, and the copper foil is prone to generate internal stress while the bonding force is poor, resulting in the copper foil being easily broken when the circuit board is collided, affecting product performance.

[0004] The embodiment of the present application provides a copper-tin alloy copper foil, the copper-tin alloy copper foil is used for a circuit board, the circuit board includes a substrate layer, a copper-tin alloy copper foil and a circuit structure layer; A crack structure is etched in the copper-tin alloy copper foil, and the crack structure includes a plurality of striped crack portions arranged in an array, the sides of each striped crack portion are irregularly curved, and the cross-section of the striped crack portion is bowl-shaped, and a convex portion is formed around the striped crack portion, the average inner diameter of the convex portion is smaller than the width of the striped crack portion, and the height of the convex portion is smaller than the recessed depth of the striped crack portion.

[0005] In an optional embodiment, the average inner diameter of the striped crack portion is greater than 15 um, and the average inner diameter of the protrusion portion is greater than 5 um.

[0006] In an optional embodiment, the depth of the striped crack portion is less than 8 um.

[0007] In an optional embodiment, the area of ​​the copper foil is S, the average curvature of the striped crack portion is q, and the number of the striped crack portions is ,in , α is a positive exponent, which indicates the influence of curvature on the area, and k is a constant, which indicates the area of ​​the striped crack when the curvature is 1.

[0008] In an optional embodiment, if the area of ​​the copper foil is S, and S is greater than a set threshold, among the multiple striped crack portions, a connecting portion is formed between two adjacent striped crack portions by laser etching, and the average inner diameter of the connecting portion is the same as the average inner diameter of the striped crack portion, and the average curvature of the connecting portion is the same as the average curvature of the striped crack portion.

[0009] In an optional embodiment, the curvature of each of the striped crack portions is different, and the position of the maximum curvature of each of the striped crack portions is different.

[0010] The present application embodiment further provides a method for preparing a copper-tin alloy copper foil, comprising: A copper-tin alloy thin film sheet is obtained by electrolysis; Etching the crack structure in the copper-tin alloy thin film by a laser etching method to obtain a copper-tin alloy copper foil; The surface of the copper-tin alloy copper foil on which the crack structure is etched is roughened.

[0011] In an optional embodiment, during the process of forming each stripe crack portion, the curvature at each position of each stripe crack portion is adjusted by adjusting the dwell time of the laser emission head.

[0012] An embodiment of the present application further provides a circuit board, including a circuit board body and at least one electronic component configured on the circuit board body, the circuit board body including a first circuit board layer and a second circuit board layer, and the copper-tin alloy copper foil as described above is combined between the first circuit board layer and the second circuit board layer.

[0013] An embodiment of the present application further provides a circuit device, including a housing and the circuit board as described above, wherein the circuit board is placed inside the housing.

[0014] Beneficial Effects It can be seen from the above technical scheme that the present application provides a copper-tin alloy copper foil, method, circuit board and device based on thermal stability. Before preparing the copper foil roughening layer, the present application first etches a crack structure in the copper-tin alloy thin film by a laser etching method to obtain a copper-tin alloy copper foil. The crack structure includes a plurality of striped crack portions arranged in an array, the side of each striped crack portion is an irregular curve, and the cross-section of the striped crack portion is bowl-shaped. A convex portion is formed around the striped crack portion, the average inner diameter of the convex portion is smaller than the width of the striped crack portion, and the height of the convex portion is smaller than the recessed depth of the striped crack portion. In this way, the striped crack portion forms a buffer structure, and the convex portion formed by preparing the striped crack portion provides support for the deformation difference caused by the insulating layer entering the buffer structure. When bonding with the insulating layer of the printed circuit board, the insulating layer can be squeezed and dispersedly enter the buffer structure, so that the copper foil will not be deformed when bonding with the insulating layer. The combination of can not only form a buffer in a more dispersed manner, but also the striped crack part has a stable positioning function, so that there will be no displacement between the copper foil and the insulating layer during the use of the circuit board. Furthermore, the present application can solve the problem that the copper foil is fixed in the printed circuit board due to the roughened surface, which forms a force, so that the printed circuit board is easily deformed during long-term use, and the copper foil is prone to generate internal stress while the bonding force is poor, which causes the copper foil to easily break when the circuit board is collided, affecting the product performance. A dispersed buffer structure is formed before roughening, and after roughening, the roughened protrusions further cooperate with the protrusions of the present application to combine with the insulating layer to "squeeze" the insulating layer, so that the extruded insulating layer can enter the crack structure of the present application, and the extruded part of the insulating layer will not form a large force on the main structure of the copper foil, and the buffer combination of the striped crack part and the protrusion itself can absorb part of the stress influence, so it can avoid the problem that the copper foil is prone to generate internal stress, which causes the copper foil to easily break when the circuit board is collided. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0016] Figure 1 It is a schematic diagram of the preparation method of the copper-tin alloy copper foil in the embodiment of the present application.

[0017] Figure 2 It is one of the structural schematic diagrams of the copper-tin alloy copper foil in the embodiment of the present application.

[0018] Figure 3This is the second structural schematic diagram of the copper-tin alloy copper foil in the embodiment of the present application. DETAILED DESCRIPTION

[0019] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0020] In addition, the terms "first" and "second" are used for descriptive purposes only and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "multiple" is two or more, unless otherwise clearly and specifically defined. It should be noted that the anilox roller, manufacturing method and tempered glass of the tempered glass disclosed in the present application can be used in the field of display technology, and can also be used in any field except the field of display technology. The application field of the anilox roller, manufacturing method and tempered glass of the tempered glass disclosed in the present application is not limited.

[0021] The present application provides a method for preparing a copper-tin alloy copper foil, wherein the copper-tin alloy copper foil is used for a circuit board, and the circuit board includes a substrate layer, a copper-tin alloy copper foil and a circuit structure layer, such as Figure 1 As shown, the copper-tin alloy copper foil comprises: S1: obtaining a copper-tin alloy thin film by electrolysis; S2: etching a crack structure in the copper-tin alloy thin film by a laser etching method to obtain a copper-tin alloy copper foil, wherein the crack structure comprises a plurality of striped crack portions arranged in an array, the side of each striped crack portion is an irregular curve, and the cross section of the striped crack portion is bowl-shaped, a convex portion is formed around the striped crack portion, the average inner diameter of the convex portion is smaller than the width of the striped crack portion, and the height of the convex portion is smaller than the concave depth of the striped crack portion; S3: performing a roughening treatment on the surface of the copper-tin alloy copper foil on which the crack structure is etched.

[0022] The present application provides a method for preparing a copper-tin alloy copper foil. Before preparing a copper foil roughening layer, the present application first etches a crack structure in the copper-tin alloy thin film by a laser etching method to obtain a copper-tin alloy copper foil. The crack structure includes a plurality of striped crack portions arranged in an array, the sides of each striped crack portion are irregularly curved, and the cross-section of the striped crack portion is bowl-shaped. A convex portion is formed around the striped crack portion, the average inner diameter of the convex portion is smaller than the width of the striped crack portion, and the height of the convex portion is smaller than the recessed depth of the striped crack portion. In this way, the striped crack portion forms a buffer structure, and the convex portion formed by preparing the striped crack portion provides support for the deformation difference caused by the insulating layer entering the buffer structure. When bonding with the insulating layer of a printed circuit board, the insulating layer can be squeezed and dispersedly enter the buffer structure, so that the copper foil will not be deformed when bonding with the insulating layer. Through the combination of the striped crack portion and the convex portion, not only can the striped crack portion be more In order to form a buffer in a dispersed manner, the striped crack part also has a stable positioning function, so that there will be no displacement between the copper foil and the insulating layer during the use of the circuit board. Furthermore, the present application can solve the problem that the copper foil is fixed in the printed circuit board due to the roughened surface, which forms a force, so that the printed circuit board is easily deformed after long-term use, and the copper foil is prone to generate internal stress while the bonding force is poor, which causes the copper foil to break easily when the circuit board is collided, affecting the product performance. A dispersed buffer structure is formed before roughening. After roughening, the roughened protrusions further cooperate with the protruding parts to combine with the insulating layer to "squeeze" the insulating layer, so that the squeezed insulating layer can enter the crack structure of the present application. The squeezed part of the insulating layer will not form a large force on the main structure of the copper foil, and the buffer combination of the striped crack part and the protruding part itself can absorb part of the stress influence, so it can avoid the problem that the copper foil is prone to generate internal stress, which causes the copper foil to break easily when the circuit board is collided.

[0023] Specifically, in an optional embodiment, the step of obtaining the copper-tin alloy thin film by electrolysis includes: A solution containing copper sulfate and tin sulfate is electrolyzed in an electrolytic cell, wherein the electrolytic cell uses an insoluble material as an anode, and the electrolytic cell uses a cathode roller whose bottom is immersed in the copper sulfate and tin sulfate electrolyte and rotates at a constant speed as a cathode, and the copper and tin in the solution are deposited on the surface of the cathode roller to form a copper-tin alloy film.

[0024] Specifically, this embodiment describes specific parameters and steps for depositing a copper-tin alloy film on an anode made of an insoluble material and a rotating cathode roller by electrolysis in a mixed electrolyte of copper sulfate (CuSO4) and tin sulfate (SnSO4).

[0025] First, prepare the equipment: Electrolytic cell: Made of corrosion-resistant stainless steel, with an insulating layer coated inside to prevent current short circuit.

[0026] Anode: A square anode made of an insoluble material (such as platinum or titanium) with an area of ​​120 cm².

[0027] Cathode: A roller made of stainless steel or other corrosion-resistant materials, with a diameter of 10 cm and a length of 30 cm.

[0028] Then proceed with the electrolyte configuration: Solution ratio: copper sulfate solution: 0.5 M, tin sulfate solution: 0.2 M.

[0029] After mixing, ensure that the pH of the solution is maintained between 2-3 to improve deposition uniformity.

[0030] Then set the electrolysis parameters: Current density: Set to 5 mA / cm² to ensure uniform coating over a large area.

[0031] Electrolysis time: 6 hours, the time can be adjusted according to the required film thickness.

[0032] Temperature control: Keep the electrolyte temperature at 25±2°C to stabilize the chemical reaction rate.

[0033] Stirring speed: The electrolyte was stirred at a constant speed of 300 rpm by a pump to improve ion mobility.

[0034] Finally, the electrolysis process is carried out: First, turn off the power supply to ensure that there is no short circuit between the anode and cathode, and then fill the electrolytic cell with the mixed electrolyte. Then turn on the cathode roller and rotate it at a constant speed (set to 1 rpm) to form a uniform flow layer on the cathode surface to promote uniform deposition. Finally, turn on the power supply to pass the current through the electrolytic cell to start the electrolysis reaction.

[0035] It should be noted that after the electrolysis is completed, the power supply is turned off, the roller is taken out, gently washed with deionized water to remove the residual electrolyte, and dried using a hot air dryer with the temperature set to 60°C for 30 minutes to obtain the electrolyzed copper foil film.

[0036] It should be noted that the electrolysis process of the present application can adopt an existing electrolysis process, and the present application does not impose any limitation on this.

[0037] Furthermore, in the process of forming each stripe crack portion, the curvature at each position of each stripe crack portion is adjusted by adjusting the dwell time of the laser emitter head. For example, the longer the dwell time of the laser emitter head is, the greater the width of the corresponding stripe crack portion is, and a more curved structure is formed here, thereby increasing the curvature.

[0038] It should be noted that the copper-tin alloy of the present application has a high laser absorption rate, but poor thermal stability. In view of the poor thermal stability, the present application utilizes the heat generated during laser etching to expand the crack structure. The temperature of the etching point of the laser etching is specific, so that the cross-section of the crack structure of the present application presents a "boat shape", which can match the deformation characteristics of the insulating layer of the circuit board when it is deformed. At the same time, due to the poor thermal stability of the copper-tin alloy of the present application, when a crack structure is formed during laser etching, tiny protrusions will be formed around the crack structure due to the inability to dissipate thermal stress. In this way, when the insulating layer is joined, the insulating layer is pressed so that the insulating layer is squeezed into the crack structure under the action of the tiny protrusions, and the crack structure then provides the function of accommodating the insulating layer. That is, in specific use, due to the thermal stability characteristics of the copper-tin alloy, the crack structure of the present application and the tiny protrusions are in a state of "mutual buffering".

[0039] The copper-tin alloy copper foil prepared by the above process of this application has a tin content of no more than 5% of the tin bronze alloy copper foil, and sometimes phosphorus, lead and other elements are added. Tensile strength σb (MPa): ≥275 (MPa), elongation δ5: ≥9%, hardness: ≥500HB (Brinell hardness); its mass resistivity is not greater than 0.180Ω·g / ㎡. Of course, the performance of the copper-tin alloy copper foil of this application is based on its raw materials, and this application will not elaborate on this.

[0040] The embodiment of the present application further provides a copper-tin alloy copper foil. Specifically, the copper-tin alloy copper foil is used for a circuit board. The circuit board includes a substrate layer, a copper-tin alloy copper foil and a circuit structure layer. A crack structure is etched in the copper-tin alloy copper foil. The crack structure includes a plurality of striped crack portions arranged in an array. The sides of each striped crack portion are irregularly curved, and the cross-section of the striped crack portion is bowl-shaped. A protrusion is formed around the striped crack portion. The average inner diameter of the protrusion is smaller than the width of the striped crack portion, and the height of the protrusion is smaller than the depth of the depression of the striped crack portion.

[0041] Combine the following Figure 2 and Figure 3 , the above-mentioned crack structure of the present application is described in detail.

[0042] The crack structure includes a plurality of striped crack portions 12 arranged in an array, the side of each striped crack portion 12 is an irregular curve, and the cross-section of the striped crack portion is bowl-shaped, a convex portion is formed around the striped crack portion, the average inner diameter of the convex portion is smaller than the width of the striped crack portion, and the height of the convex portion is smaller than the recessed depth of the striped crack portion.

[0043] Specifically, Figure 2As shown, the stripe cracks in the present application can be arranged in an array, so as to be gradually distributed on the entire copper foil. Figure 2 and Figure 3 The example is only an example for the purpose of explanation. In actual situations, the crack structure may be more complex in form and structure, which will not be elaborated in this application.

[0044] In an optional embodiment, the average inner diameter of the striped crack portion 12 is greater than 15um, and the average inner diameter of the protrusion 13 is greater than 5um, wherein the average inner diameters of the striped crack portion 12 and the protrusion 13 are the same or different. In this way, the average inner diameter of the striped crack portion 12 and the average inner diameter of the protrusion 13 have a preferred size range, which is conducive to providing a more suitable replacement space.

[0045] It should be noted that the striped crack portion 12 of the present application further plays a role in positioning and fixing. When the insulating layer is combined, the position of the insulating layer and the layer structure of the present application can be further limited by the structure, and it is not easy to form a misalignment.

[0046] In an optional embodiment, the depth of the stripe crack portion 12 is less than 8 um. In this way, the depth of the depression is within a reasonable range, so that the depth is controlled within 8 um, and the copper foil will not be more easily broken due to excessive depth.

[0047] In an optional embodiment, the area of ​​the copper foil is S, the average curvature of the striped crack portion is q, and the number of the striped crack portions is ,in , α is a positive exponent, indicating the influence of curvature on the area, and k is a constant, indicating the area of ​​the stripe crack when the curvature is 1. In this embodiment, the stripe crack quantity model is used. , where A_stripe(q) is inversely proportional to q, so that when the average curvature is larger, the corresponding striped crack portion has more locations with the largest bending, or the area with the largest bending is larger, so that more space can be provided to accommodate the insulating layer, and the more bending, the more complex the force distribution of the insulating layer trapped in the striped crack portion, which is more conducive to firm fixation.

[0048] In an optional embodiment, if the area of ​​the copper foil is S, and S is greater than a set threshold, a connecting portion is formed between two adjacent striped crack portions among the multiple striped crack portions by laser etching, and the average inner diameter of the connecting portion is the same as the average inner diameter of the striped crack portion, and the average curvature of the connecting portion is the same as the average curvature of the striped crack portion. In this embodiment, when S is greater than the set threshold, it means that the copper foil area is large. At this time, the distance between the two striped crack portions 12 may be too far. Then, by setting the connecting portion, the striped crack portions 12 with a relatively long distance are connected, thereby improving the uniformity of local dispersion and avoiding the problem of uneven force due to uneven local dispersion when subsequently bonding with the insulating layer.

[0049] In an optional embodiment, the curvature of each of the striped crack portions is different, and the position of the maximum curvature of each of the striped crack portions is different. In this way, the overall force on the insulating layer is more complex, which is conducive to structural stability.

[0050] In an optional embodiment, the step of roughening the surface of the copper-tin alloy copper foil on one side where the crack structure is etched includes: A rough protrusion is formed on one side surface of the crack structure by electrolyzing a diluted copper sulfate solution.

[0051] In addition, further, the present application also provides a circuit board, including a circuit board body and at least one electronic component configured on the circuit board body, the circuit board body includes a first circuit board layer and a second circuit board layer, and the copper-tin alloy copper foil as described above is combined between the first circuit board layer and the second circuit board layer.

[0052] In addition, further, the present application also provides a circuit device, including a housing and the circuit board as described above, wherein the circuit board is placed inside the housing.

[0053] The circuit device of the present application may be a terminal device, an electronic device, etc., and the present application does not impose any limitation on this.

[0054] It should be noted that the copper-tin alloy copper foil embodiments and manufacturing method embodiments provided in the embodiments of the present invention can be referenced to each other, and the embodiments of the present application are not limited to this. Any technician familiar with the technical field can easily think of changes within the technical scope disclosed in the present application, and they should be included in the protection scope of the present application. Therefore, they will not be repeated. The above is only an optional embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A copper-tin alloy copper foil, characterized in that: The copper-tin alloy copper foil is used for a circuit board, and the circuit board comprises a substrate layer, a copper-tin alloy copper foil and a circuit structure layer; A crack structure is etched in the copper-tin alloy copper foil, and the crack structure includes a plurality of striped crack portions arranged in an array, the sides of each striped crack portion are irregularly curved, and the cross-section of the striped crack portion is bowl-shaped, and a convex portion is formed around the striped crack portion, the average inner diameter of the convex portion is smaller than the width of the striped crack portion, and the height of the convex portion is smaller than the recessed depth of the striped crack portion.

2. The copper-tin alloy copper foil according to claim 1, characterized in that: The average inner diameter of the striped crack portion is greater than 15um, and the average inner diameter of the protrusion portion is greater than 5um.

3. The copper-tin alloy copper foil according to claim 1, characterized in that: The depth of the stripe crack portion is less than 8 um.

4. The copper-tin alloy copper foil according to claim 1, characterized in that: The area of ​​the copper foil is S, the average curvature of the striped crack portion is q, and the number of the striped crack portions is: ,in , α is a positive exponent, which indicates the influence of curvature on the area, and k is a constant, which indicates the area of ​​the striped crack when the curvature is 1.

5. The copper-tin alloy copper foil according to claim 1, characterized in that: If the area of ​​the copper foil is S, and S is greater than a set threshold, among the multiple striped crack portions, a connecting portion is formed between two adjacent striped crack portions by laser etching, and the average inner diameter of the connecting portion is the same as the average inner diameter of the striped crack portion, and the average curvature of the connecting portion is the same as the average curvature of the striped crack portion.

6. The copper-tin alloy copper foil according to claim 1, characterized in that: The curvature of each of the striped crack portions is different, and the position where the maximum curvature of each of the striped crack portions is located is different.

7. A method for preparing a copper-tin alloy copper foil as claimed in claim 1, characterized in that: include: A copper-tin alloy thin film sheet is obtained by electrolysis; Etching the crack structure in the copper-tin alloy thin film by a laser etching method to obtain a copper-tin alloy copper foil; The surface of the copper-tin alloy copper foil on which the crack structure is etched is roughened.

8. The preparation method according to claim 7, characterized in that: In the process of forming each stripe crack portion, the curvature at each position of each stripe crack portion is adjusted by adjusting the dwell time of the laser emitting head.

9. A circuit board, characterized in that: It comprises a circuit board body and at least one electronic component arranged on the circuit board body, wherein the circuit board body comprises a first circuit board layer and a second circuit board layer, and the copper-tin alloy copper foil as claimed in any one of claims 1 to 6 is combined between the first circuit board layer and the second circuit board layer.

10. A circuit device, characterized in that: It comprises a housing and the circuit board as claimed in claim 9, wherein the circuit board is placed inside the housing.

Citation Information

Patent Citations

  • Method for improving bonding force of laminated base material and laminated conductor layer in semi-additive process (SAP)

    CN102307437A

  • Flexible copper-clad plate and printed circuit board

    CN114919255A

  • Ultra-thin copper foil with carrier and printed wiring board using ultra-thin copper foil with carrier

    CN1620221A

  • Rolled copper foil, its manufacturing method, and flexible printed board using the rolled copper foil

    JP2008086999A

  • Copper foil with carrier, and printed wiring board, printed circuit board and copper-clad laminate, using same

    TW201438889A

Cited By

  • Machining method for improving carrier plate quality through laser drilling

    CN121057111A